A KOHA customization, migration, and training project for the Quezon City Public Library - Corral, Valerie Darl M.; Piquero, Giancarlo M.; Dorado, Dan Anthony D. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
The Quezon City Public Library (QCPL) is the largest public library in Metro Manila and serves nearly 2.679 million residents through its main library located at the back of Quezon City Hall and 21 branch libraries distributed all over the city. As a part of its commitment to continue to provide its users a wide variety of quality programs and services, the QCPL is upgrading its integrated library system (ILS)-- primarily to enhance its online public access catalog (OPAC) and automate select processes involved in everyday library work.
The National Library of the Philippines (NLP) recommends Koha, the first open source ILS created in 1999 by Katipo Communications for the Horowhenua Library Trust in New Zealand, for all affiliated public libraries in the country and offers relevant assistance and training through its Information Technology Division. The QCPL, with its autonomy in implementing its own policies and projects, decided to migrate from OpenBiblio, its current ILS since 2006, to Koha, but not without some challenges that prompted the postponement of its initial efforts in late 2011, such as: (1) the bibliographic data in OpenBiblio cannot be exported and directly migrated to Koha, (2) there is a need for additional workforce in terms of encoding the records, and (3) lack of immediate technical assistance with the migration to Koha to suit the needs and preferences of the library staff and users among others.
Through the use of survey questionnaires, semi-structured interviews, and user-centered system design (UCSD), the current ILS underwent systems analysis and evaluation in preparation for the customization, migration, and implementation of the new ILS. A training program about Koha was also conducted to supplement the skill sets of the library staff and to assist them in the transition of upgrading the ILS. The participants were the Multimedia and Internet Services (MIS) section, who will administer and manage the new ILS, and the Technical Services section, who will be the primary users of the new ILS among the library staff.
The study found out that there is also a need to increase the awareness about the OPAC, as the data gathered reflected that the service is not visible enough to the users. The QCPL administration preferred that the customization and training focus first on the OPAC and Cataloging modules, while the library staff gains practical familiarity with the rest of the features and functionalities of Koha. Further training is set to be conducted wherein the topic focuses on the modules and features directly related to a particular section. Once the QCPL is able to improve and sustain the OPAC, continue with the customization, and consider other modules to capitalize on the potential offered by Koha, everything will eventually translate to a more holistic and better quality of service for the users.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Quezon City Public Library; Integrated library systems (Computer systems) -- Philippines -- Quezon City